Measuring older people's socioeconomic position: a scoping review of studies of self-rated health, health service and social care use. Issue 6 (15th March 2022) - Spiers, Gemma Frances; Liddle, Jennifer E; Stow, Daniel; Searle, Ben; Whitehead, Ishbel Orla; Kingston, Andrew; Moffatt, Suzanne; Matthews, Fiona E; Hanratty, Barbara
Abstract : Background: The challenges of measuring socioeconomic position in older populations were first set out two decades ago. However, the question of how best to measure older people's socioeconomic position remains pertinent as populations age and health inequalities widen. Methods: A scoping review aimed to identify and appraise measures of socioeconomic position used in studies of health inequalities in older populations in high-income countries. Medline, Scopus, EMBASE, HMIC and references lists of systematic reviews were searched for observational studies of socioeconomic health inequalities in adults aged 60 years and over, published between 2000 and 2020. A narrative synthesis was conducted. Findings: One-hundred and thirty-eight studies were included; 20 approaches to measuring socioeconomic position were identified. Few studies considered which pathways the chosen measures of socioeconomic position intended to capture. The validity of subjective socioeconomic position measures, and measures that assume shared income and educational capital, should be verified in older populations. Incomplete financial data risk under-representation of some older groups when missing data are socially patterned. Older study samples were largely homogeneous on measures of housing tenure, and to a lesser extent, measures of educational attainment. Measures that use only two response categories risk missing subtle differences in older people's socioeconomic circumstances. Conclusion: Poor choice of measures of socioeconomic position risk underestimating the size of health inequalities in older populations. Choice of measures should be shaped by considerations of theory, context and response categories that detect subtle, yet important, inequalities. Further evidence is required to ascertain the validity of some measures identified in this review.